(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The beginning of recorded history, it has been known that human people have utilized art to express elements that transcend the spoken and the written word, in order to convey the condition of their inner mental landscapes. Art is inherently healing and has the power to change. Transpersonal Art Therapy takes one step beyond conventional art therapy and digs into soul of the individual beyond the boundaries of his/her personal identity. This article offers a systematic assessment of the literature, pointing out the merits, critiques, and subsequently, the first author’s own personal thoughts about connection with art. This is followed by introspective thoughts on art movements, by giving quintessential instances to demonstrate the effect of prototype work representing various art movements and their impact on the irst author’s psychology. Future ramifications of the study are addressed along with areas in which there are large gaps in empirical data, which thus need to be studied. Transpersonal art therapy is both a method of thinking and a way of doing things. It recognizes spirituality as universal across nations and history, compelling to include spiritual in scope evaluation and treatment, and pushes us to strive for a balance of mind, body, emotions, and spirit in everyone treat, beginning with ourselves.